Light-evoked somatosensory perception of transgenic rats that express channelrhodopsin-2 in dorsal root ganglion cells. - Zhi-Gang Ji (PLoS ONE, 2012)
In vertebrate somatosensory systems, each mode of touch-pressure, temperature or pain is sensed by sensory endings of different dorsal root ganglion (DRG) neurons, which conducted to the specific cortical loci as nerve impulses. Therefore, direct electrical stimulation of the peripheral nerve endings causes an erroneous sensation to be conducted by the nerve. We have recently generated several transgenic lines of rat in which channelrhodopsin-2 (ChR2) transgene is driven by the Thy-1.2 promoter. In one of them, W-TChR2V4, some neurons were endowed with photosensitivity by the introduction of the ChR2 gene, coding an algal photoreceptor molecule. The DRG neurons expressing ChR2 were immunohistochemically identified using specific antibodies to the markers of mechanoreceptive or nociceptive neurons. Their peripheral nerve endings in the plantar skin as well as the central endings in the spinal cord were also examined. We identified that ChR2 is expressed in a certain population of large neurons in the DRG of W-TChR2V4. On the basis of their morphology and molecular markers, these neurons were classified as mechanoreceptive but not nociceptive. ChR2 was also distributed in their peripheral sensory nerve endings, some of which were closely associated with CK20-positive cells to form Merkel cell-neurite complexes or with S-100-positive cells to form structures like Meissner's corpuscles. These nerve endings are thus suggested to be involved in the sensing of touch. Each W-TChR2V4 rat showed a sensory-evoked behavior in response to blue LED flashes on the plantar skin. It is thus suggested that each rat acquired an unusual sensory modality of sensing blue light through the skin as touch-pressure. This light-evoked somatosensory perception should facilitate study of how the complex tactile sense emerges in the brain.